South Australian facial trauma: a population analysis of social economic deprivation and facial fractures: part one - Jason Diab; Benjamin Grave; Walter Flapper; Peter Anderson; David J David; Mark Moore (Australasian Journal of Plastic Surgery)
**Background**: Trauma remains a leading cause of morbidity and mortality in Australia. The objective of this South Australian study was to analyse epidemiological trends in facial fractures and assess the relationship between socioeconomic disadvantage and clinical outcomes.